Introduction to fire protection - Klinoff, Robert (Clifton Park, New York : Delmar Cengage Learning, 2012)
eflecting the latest FESHE outlines and NFPA fire codes and ordinances, an introductory text covers incident effectiveness, customer service, fire fighter emergency decision making, and life safety initiatives.
1. Fire Science Education and the Firefighter Selection Process -- 2. Fire Protection Career Opportunities -- 3. Public Fire Protection -- 4. Chemistry and Physics of Fire -- 5. Public and Private Support Organizations -- 6. Fire Department Resources -- 7. Fire Department Administration -- 8. Support Functions -- 9. Training -- 10. Fire Prevention -- 11. Codes and Ordinances -- 12. Fire Protection Systems and Equipment -- 13. Emergency Incident Management -- 14. Emergency Operations.
Includes index.
Keywords: FIRE PREVENTION